Moisture-induced elastic constants of poplar - Yılmaz Aydın, Tuğba; Aydın, Murat (Maderas. Ciencia y Tecnología, 2025)
Twelve elastic constants of Populus × canadensis, previously unavailable in the literature, were determined using ultrasonic testing.Samples were conditioned at a temperature of 20 °C ± 1 °C and 45 %, 65 %, and 85 % relative humidity. An Olympus EPOCH 650 flaw detector was used with V153-RM (1 MHz shear wave), and A133S-RM (2,25 MHz pressure wave) contact transducers. A contact medium was applied. Wave propagation times were measured along the principal directions (L, R, T), the main planes (LR, LT, RT, RL, TL, TR), and the off-axis planes (LR45°, LT45°, RT45°). Ultrasonic wave velocities were calculated across the specified directions and planes. These velocities were then used to estimate moduli (EL, ER, ET, GLR, GLT, GRT) and Poisson’s ratios (µLR, µLT, µRT, µRL, µTL, µTR) via stiffness matrix analysis. Moduli were also calculated using a simple formula multiplying the density and velocity for comparison. Elastic moduli derived from the stiffness matrix were substantially lower than those from the simple density–velocity formula, while shear moduli remained nearly identical. Both moduli steadily decreased with the increase in moisture content. Moisture content significantly affected all moduli. In contrast, Poisson’s ratios showed no consistent trend with moisture. Specifically, µLR and µRL increased linearly with moisture, while the other ratios decreased irregularly. For µRT, the effect of moisture was insignificant. Relationships between density and velocity, moduli, and Poisson’s ratios were assessed using coefficients of determination.The coefficients ranged from 0,23 to 0,56 for velocities, 0,08 to 0,37 for elasticity, 0,23 to 0,31 for shear, and 0 to 0,10 for ratios. When the coefficient was calculated within the humidity groups significant increases were observed. It was assumed that water-related increases in density did not reflect structural solidification, and therefore did not lead to improved elasric properties. This effect is explained by the well-known reduction in wave velocities caused by water, which dominates the calculations.